Effect of Iron Deficiency Anemia on Insulin Like- Growth Factor-1 Level Among Children: A Cross-Sectional Study - Usman, Muhammad; Haroon, Zujaja Hina; Khan, Muhammad Qaiser Alam; Anwar, Muhammad; Younas, Muhammad; Roghani, Maimoona (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the effect of iron deficiency anemia on the serum level of IGF-1 by comparison between low ferritin and low hemoglobin group and healthy control.Study Design: Comparative case control study.Place and Duration: Study The study was conducted at department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology, Rawalpindi, from   Jul to Dec 2022.Methodology: The case control study was done in 110 children, aged between 2-14 years. Children with short stature and iron deficiency anemia (cases) were compared to a group of age and gender matched healthy children (controls). The sample size of 110 children was calculated using WHO sample size calculator. After brief history and examination, 3ml venous blood was drawn by standard technique. Complete blood picture estimation and the estimation of IGF-1 and ferritin levels was done. Parameters of complete blood picture included were Hemoglobin in (Hb), Red blood cells (RBC), Packed cell volume (PCV), Mean corpuscular hemoglobin (MCH), Mean corpuscular volume (MCV). Data was analyzed using SPSS.  Results: Comparison of the serum levels of IGF-1, analyzed by chemiluminescent immunoassay between two groups showed lower IGF-1 levels among iron deficiency anemia group (8.60 µmol/L) as compared to control group (38.80 µmol/L) which is statistically significant (p-value